Effect of ecstasy [3,4-methylenedioxymethamphetamine (MDMA)] on cerebral blood flow: a co-registered SPECT and MRI study - Chang, Linda; Grob, Charles S.; Ernst, Thomas; Itti, Laurent; Mishkin, Fred S.; Jose-Melchor, Rosemarie; Poland, Russell E. (Psychiatry research, 2000)
3,4-Methylenedioxymethamphetamine (MDMA), an illicit recreational drug, damages serotonergic nerve endings. Since the cerebrovasculature is regulated partly by the serotonergic system, MDMA may affect cerebral blood flow (CBF) in humans. We evaluated 21 abstinent recreational MDMA users and 21 age- and gender-matched healthy subjects with brain SPECT and MRI. Ten of the MDMA subjects also had repeat SPECT and MRI after receiving two doses of MDMA. Abstinent MDMA users showed no significantly different global or regional CBF (rCBF) compared to the control subjects. However, within 3 weeks after MDMA administration, rCBF remained decreased in the visual cortex, the caudate, the superior parietal and dorsolateral frontal regions compared to baseline rCBF. The decreased rCBF tended to be more pronounced in subjects who received the higher dosage of MDMA. Two subjects who were scanned at 2–3 months after MDMA administration showed increased rather than decreased rCBF. Low-dose recreational MDMA use does not cause detectable persistent rCBF changes in humans. The lack of long-term rCBF changes may be due to a non-significant effect of serotonergic deficits on rCBF, or regeneration of serotonergic nerve terminals. The subacute decrease in rCBF after MDMA administration may be due to the direct effect of MDMA on the serotonergic system or the indirect effects of its metabolites on the dopaminergic system; the preliminary data suggest these effects may be transient.